2009
DOI: 10.1016/j.eatbeh.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Acute tryptophan depletion and sweet food consumption by overweight adults

Abstract: Serotonergic involvement has been implicated in preferential consumption of treat foods. We tested the effect of acute tryptophan depletion (ATD) on food consumption by overweight and lean adults with and without a history of recurrent major depressive disorder (MDD). ATD and taste-matched placebo challenges were administered double-blind in counter-balanced order. Participants were classified as lean (n = 36) or overweight (n=19) on the basis of body mass index (BMI). Total calorie, carbohydrate, protein, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
1
12
1
Order By: Relevance
“…On the other hand, the gut microbiota regulates both the 5-HT synthesis and its release from the enteroendocrine cells, and 5-HT plays its role on the CNS as one of the most important central neurotransmitters in the regulation of mood, sleep, and pain[ 49 ]. Consistently, modification of central 5-HT levels was shown by Pagoto et al [ 50 ] to affect food preferences. Following acute tryptophan depletion (transient decrease of both peripheral and central 5-HT levels), overweight individuals increased their sweet calorie intake and preferred sweet foods.…”
Section: Brain-liver and Blg Axissupporting
confidence: 71%
“…On the other hand, the gut microbiota regulates both the 5-HT synthesis and its release from the enteroendocrine cells, and 5-HT plays its role on the CNS as one of the most important central neurotransmitters in the regulation of mood, sleep, and pain[ 49 ]. Consistently, modification of central 5-HT levels was shown by Pagoto et al [ 50 ] to affect food preferences. Following acute tryptophan depletion (transient decrease of both peripheral and central 5-HT levels), overweight individuals increased their sweet calorie intake and preferred sweet foods.…”
Section: Brain-liver and Blg Axissupporting
confidence: 71%
“…There is also evidence to suggest a role for changes in the brain's serotonergic signalling by ELA and that these alterations may contribute to obesity and food addiction . For example, a study of 55 women showed that lowering of CNS serotonin by acute tryptophan depletion resulted in increased sweet calorie intake and a heightened preference for sweet foods in overweight but not normal weight individuals . Disruptions to these brain networks may override homeostatic needs and drive the overconsumption of highly palatable foods .…”
Section: Introductionmentioning
confidence: 99%
“…So far this has not been done. 45,67 There is good, although not definitive, evidence that effects of ATD act through depletion of serotonin, not other mechanisms. However, this has to be assessed for each outcome measure used in ATD studies.…”
Section: The Need For Positive Control Treatments and Other Strategiementioning
confidence: 99%